2015
DOI: 10.1165/rcmb.2014-0035oc
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Epithelial Cells Modifies Airway Macrophage Response to Ozone

Abstract: The initial innate immune response to ozone (O 3 ) in the lung is orchestrated by structural cells, such as epithelial cells, and resident immune cells, such as airway macrophages (Macs). We developed an epithelial cell-Mac coculture model to investigate how epithelial cell-derived signals affect Mac response to O 3 . Macs from the bronchoalveolar lavage (BAL) of healthy volunteers were cocultured with the human bronchial epithelial (16HBE) or alveolar (A549) epithelial cell lines. Cocultures, Mac monoculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
(72 reference statements)
4
25
0
Order By: Relevance
“…Effects of O 3 on Cholesterol Efflux and Cytokine Gene Expression-As expected and previously described by us (30,31), exposure to O 3 caused an inflammatory response as marked by increased gene expression (Fig. 4, A and B) and protein concentration (Fig.…”
Section: Identification Of O 3 -Induced Oxysterol Formation In Vitrosupporting
confidence: 83%
“…Effects of O 3 on Cholesterol Efflux and Cytokine Gene Expression-As expected and previously described by us (30,31), exposure to O 3 caused an inflammatory response as marked by increased gene expression (Fig. 4, A and B) and protein concentration (Fig.…”
Section: Identification Of O 3 -Induced Oxysterol Formation In Vitrosupporting
confidence: 83%
“…The cells were then exposed to 4 different concentrations of nitrogen dioxide (1 ppm, 2 ppm, 3 ppm, or 5 ppm) or ozone (0.25 ppm, 0.50 ppm, 0.75 ppm, or 1.00 ppm) for 2 hours in exposure chambers held at 37.5 °C, 5% CO 2 , and 88% relative humidity (Devlin et al, 1994, McKinnon et al, 1993, Bauer et al, 2015). Simultaneous to each NO 2 and O 3 exposure, additional cells were exposed to filtered air at the same temperature, humidity, and air flow rate that was used for the pollutant exposures; this served as our negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophages may also be activated by ambient particulate matter containing TLR activating microbial products such as lipopolysaccharide, β-glucan, bacteria and fungal spores 86 87. Bauer et al 88 showed that co-culture of human primary AMs with epithelial cells modifies macrophage responses to O 3 , enhancing M2 activation status and reducing phagocytic activity. Goto et al 89 demonstrated that cytokine production by AM in response to particulate air pollution accelerates monocyte release from the bone marrow.…”
Section: The Environment and Agingmentioning
confidence: 99%